Implementasi Digitalisasi dalam Proses Pembelajaran Kursus di Lembaga Kursus Dan Pelatihan (LKP) Widyagama Luwuk - Nur, Amal; Hamzah, Hamdan; Yusri, Yusri (Universitas Pahlawan Tuanku Tambusai, 2025)
The digitalization era is an effort to follow the development of digital technology in Indonesia. This effort has been carried out in various fields, including education. LKP Widyagama Luwuk as a non-formal educational institution implements digitalization by providing digital-based learning. The formulation of the research problem is how to apply digitalization to the learning components and learning process at LKP Widyagama Luwuk, and what are the supporting and inhibiting factors. The research approach uses qualitative descriptive. Data collection uses observation, interview, and documentation techniques. Interviews were conducted with 6 research subjects and 3 informants. The validity of the data was tested by triangulation of sources and methods. Data analysis was carried out by data collection, reduction, presentation, and conclusion. The results of the study indicate that the learning components have implemented digitalization well. The learning process is related to planning, implementation, supervision, and assessment. Planning is realized in the RPP and Syllabus based on needs and adjusting to the development of information and communication technology. Implementation takes place with offline and online models. Supervision is carried out by the manager and assessment is carried out through several tests using digital-based technology. Supporting factors for the implementation of digitalization include the existence of quality human resources, supporting institutional facilities and infrastructure, effective and efficient development of information and communication technology. While the inhibiting factors are the development of information and communication technology that is too fast, the instructor's willingness to learn is still low, the cost of procuring facilities and infrastructure is high, and some learning infrastructure is less supportive.